Game Theory in Strategic Management-Dynamic Games. Theoretical and Practical Examples - BUSU, Mihail (Management Dynamics in the Knowledge Economy, 2018)
Game Theory provides an analysis tool for describing the decision-making process of one or more players, their behavior when there are plenty of possible outcomes. Strategic behavior is a generic term that designates all concerted and consistent actions promoted by an enterprise in order to influence the competitive environment or at least to adapt to its evolution. This paper aims at exploring the real potential of strategic management based on dynamic game theory decisions and illustrates that the usefulness and power of game theory applied in strategic management lie in its ability to provide insights on competitive climate and strategies. In this paper, we will investigate some potential contributions of game theory to strategic management, especially with regard to applications in individual industries. The examples presented in the second part of the paper are based on strategic management decisions that involve dominant strategies.